OPTIMIZED APPROACH TO SOFTWARE RELEASE PLANNING WITH VOLATILE REQUIREMENTS - Gupta, S. L.; Soni, Rachna; Jolly, Ashish; Rana, Arti (European Scientific Journal, ESJ, 2012)
Software release is one of the most prominent issues involved in software development to decide upon the most appropriate software release plans. Software companies are facing many problems with endless product planning challenges, viz. availability of limited resources, resource bottlenecks, conflicting requirements, complex product dependencies, time-to-market pressures and geographically dispersed stakeholders and project teams. Release Planning is an important and essential part of any type of Software Release Management. The present paper works on complexity of Release Planning with conflicting requirements, contentment of the stakeholders to condense the cost of on the whole software release process.